واقع التكلفة التعليمية لمرحلة التعليم الأساسي في محافظة إب بالجمهورية اليمنية - المطرى، ماجد محمد أحمد (جامعة الجزيرة, 2019)
يهدف البحث إلى التعرف على واقع التكلفة التعليمية في مرحلة التعليم الأساسي العام بمحافظة إب خلال الفترة من العام المالي2010 – 2013م بالأسعار الجارية والثابتة واستخراج متوسط تكلفة التلميذ الملتحق بالأسعار الجارية والثابتة، ومقارنة متوسطات التكلفة التعليمية لمرحلة التعليم الأساسي بحسب المنطقة الجغرافية (حضر-ريف). ولتحقيق ذلك تم استخدام المنهج الوصفي بنوعيه (المسحي والوثائقي)، وقد تكون مجتمع البحث وعينته من جميع مدارس التعليم الأساسي العام بالمديريات (أساسية فقط، ثانوية/ أساسي)، (ذكور، إناث، مختلط)، والإدارات التعليمية بالمديريات، والمركز الرئيسي بالمحافظة (مكتب التربية والتعليم)، وإعداد التلاميذ الملتحقين في مرحلة الأساسي وقد اعتمد البحث على العديد من الأدوات العلمية منها السجلات والإحصاءات الرسمية، والمراجع والمصادر العلمية المتخصصة في موضوع البحث، وبعد تحليلها تم التوصل إلى العديد من النتائج، أهمها: - بلغ متوسط التكلفة التعليمية في مرحلة التعليم الأساسي العام بمحافظة إب خلال الفترة من العام الدراسي بالأسعار 2010/2011م- 013/2012م (25,690,374,538 -19,456,990,782) ريال يمني بالأسعار الجارية والثابتة على التوالي. - بلغ متوسط تكلفة التلميذ الواحد الملتحق خلال الفترة (42، 879 -32، 475) ريال يمني بالأسعار الجارية والثابتة على التوالي. وقد توصل البحث إلى العديد من الاستنتاجات والتوصيات والمقترحات.
This research aim at identifying the cost of education in general basic education stage in Ibb governorate during the period from the academic year 2010/2011 to 2012/2013 at current and constant prices and finding the cost of a student enrolled in current and constant prices during the period through analysing final accounts reports of Education Office in Ibb governorate and analysing official statistics of numbers of students for the same. To achieve research aims, the descriptive methodology was used in both approaches (survey and documentary). The research population and its sample has consisted of all general basic education schools in directorates of Ibb governorate (only primary, primary and secondary), (male, female, mixed). Moreover, educational departments in directorates, Education Office of Ibb Governorate as well. The current research has used many scientific tools, including: official records and statistics, references and scientific sources specialized in research subject. After analysing, the research has reached many results, most notably: 1. The average of educational cost in the general basic education stage in Ibb Governorate during the period from the academic year 2010/2011 to 2012-2013 was (25,690,374,538 -19,456,990,782) YR at current and constant prices, respectively. 2. The average cost of a student enrolled during the period was - 20690, ((906204 YR at current and constant prices, respectively. 3. Finlay, the research has reached many conclusions, recommendations and suggestions.
Keywords: التكلفة التعليمية -- المؤسسات التربوية -- التعليم الأساسي -- اليمن